Relationships between cohesion, collective efficacy and performance in professional basketball teams: An examination of mediating effects - Heuze, J. P.; Raimbault, N.; Fontayne, P. (Journal of Sports Sciences, 2006)
The main aim of this study was to examine mediating effects in the relationships between cohesion, collective efficacy and performance in professional basketball teams. A secondary aim was to examine the correlates of collective efficacy in a professional sport. A total of 154 French and foreign professional players completed French or English versions of questionnaires about cohesion and collective efficacy. Two composite measures of individual performance were used (pre- and post-performance). Individual-level analyses were performed. Regression analyses supported two mediating relationships with collective efficacy as a mediator of the pre-performance - Group integration-task relationship, and Group integration-task as a mediator of the pre-performance - collective efficacy relationship. Statistical analyses indicated that neither Group integration-task nor collective efficacy was a better mediator in the relationship between pre-performance and the other group variables. Results also revealed positive relationships between three dimensions of cohesion (i.e. Individual attractions to the group-task, Group integration-task, Group integration-social) and collective efficacy. These findings suggest that in professional basketball teams, staff members should look after athletes who perform at a lower or below their usual level because their performances might lead them into a downward cohesion - collective efficacy spiral. Staff members should also develop a high quality of group functioning, both on and off the basketball court, given its relationship with collective efficacy.